BookmarkSubscribeRSS Feed
☑ This topic is solved. Need further help from the community? Please sign in and ask a new question.
whymath
Lapis Lazuli | Level 10

This task is going to derive a time-series variable, The rule is:

X(t) = 1.5 * X(t-1) - 0.5 * X(t-2) + e;
X(1) = e;
X(2) = 1.5 * X(1) + e;

where e follows a standard normal distribution. Here is how I generate this sequence:

data have;
  call streaminit(42);
  do i=1 to 200;
    e=rand("normal",0,1);
    output;
  end;
run;

data want;
  set have;

  *Method 1;
  x+sum(0.5*x,-0.5*lag(x),e);

  *Method 2;
  y+0.5*y-0.5*lag(y)+e;

  *Method 3;
  retain z;
  if _n_=1 then z=e;
  if _n_=2 then z=1.5*z+e;

  lag2_z=lag2(z);
  if _n_>2 then z=1.5*z-0.5*lag2_z+e;
run;

Run this code, I just find only result of method 1 is right. Why Method 2 and Method 3 are wrong? How to fix them?

Thank you for any hint.

1 ACCEPTED SOLUTION

Accepted Solutions
s_lassen
Meteorite | Level 14

With method 2, the problem is simply that the expression 

y+0.5*y-0.5*lag(y)+e;

is to be understood as 

y+(0.5*y-0.5*lag(y)+e);

which in the first iteration will set Y to 0 (the SUM statement, "Y+..." will initialize Y to 0, retain Y, and add whatever is after the plus sign, like

retain y 0;
y=sum(y,0.5*y-0.5*lag(y)+e);

But the second parameter evaluates to a missing value, meaning that Y stays 0 in the first iteration.

 

The method 1 calculation, on the other hand, is equivalent to 

retain x 0;
x=sum(x,0.5*x,-0.5*lag(x),e);

which will set X to E on the first iteration.

 

In method 3, the problem is that you calculate Z before taking the LAG2 function the first two times, but after the LAG2 call the remaining times. Method 3 can be rewritten as e.g.

  retain z;

  lag2_z=lag(z);

  if _n_=1 then z=e;
  else if _n_=2 then z=1.5*z+e;
  else z=1.5*z-0.5*lag2_z+e;

Note that I changed from LAG2 to LAG, as the LAG call now always comes first.

View solution in original post

2 REPLIES 2
s_lassen
Meteorite | Level 14

With method 2, the problem is simply that the expression 

y+0.5*y-0.5*lag(y)+e;

is to be understood as 

y+(0.5*y-0.5*lag(y)+e);

which in the first iteration will set Y to 0 (the SUM statement, "Y+..." will initialize Y to 0, retain Y, and add whatever is after the plus sign, like

retain y 0;
y=sum(y,0.5*y-0.5*lag(y)+e);

But the second parameter evaluates to a missing value, meaning that Y stays 0 in the first iteration.

 

The method 1 calculation, on the other hand, is equivalent to 

retain x 0;
x=sum(x,0.5*x,-0.5*lag(x),e);

which will set X to E on the first iteration.

 

In method 3, the problem is that you calculate Z before taking the LAG2 function the first two times, but after the LAG2 call the remaining times. Method 3 can be rewritten as e.g.

  retain z;

  lag2_z=lag(z);

  if _n_=1 then z=e;
  else if _n_=2 then z=1.5*z+e;
  else z=1.5*z-0.5*lag2_z+e;

Note that I changed from LAG2 to LAG, as the LAG call now always comes first.

whymath
Lapis Lazuli | Level 10
Thank you very much, very detailed.

SAS Innovate 2025: Save the Date

 SAS Innovate 2025 is scheduled for May 6-9 in Orlando, FL. Sign up to be first to learn about the agenda and registration!

Save the date!

How to Concatenate Values

Learn how use the CAT functions in SAS to join values from multiple variables into a single value.

Find more tutorials on the SAS Users YouTube channel.

SAS Training: Just a Click Away

 Ready to level-up your skills? Choose your own adventure.

Browse our catalog!

Discussion stats
  • 2 replies
  • 394 views
  • 3 likes
  • 2 in conversation